Optimasi Pemasangan Jalur Pipa Air Bersih Melalui Minimum Spanning Tree Dengan Algoritma Prim - Rina Filia Sari; Rina Widyasari; Fithria Aidra Marpaung (Universitas Islam Raden Rahmat, Malang, 2023)
Water is a very important need for human survival, without water there will be no life on earth. Because of the importance of the need for clean water, it’s natural if the clean water sector gets priority main handling because it involves the lives of many people. There are many ways to get clean water, one of which is by installing the pipes of clean water will be done in Kwala Air Hitam Village. The issue of pipe installation this clean water can be overcome through the Minimum Spanning Tree approach pipe installation can be more optimal. Search for the Minimum Spanning Tree using the prim algorithm manually. The research aims to get a minimum cost of installation of clean water pipes through Minimum Spanning Tree uses Prim Algorithm. The Prim Algorithm is a algorithm in the graph theory to find a minimal range tree for a graph which is connected to each other. In the results of research the Minimum Spanning Tree using the Prim Algorithm manually is obtained in total the length of the pipe which will be installed is 9.806 metres with 52 points and 56 sides. And the first graph had 52 points and 59 sides with a length of the pipes are 9.969 metres. So, the minimum fee amount Rp. 1.732.850.000 (one billion seven hundred thirty two million eight hundred fifty thousand rupiahs).